Simulation of Waste Load Variations on Stress Analysis Results of Incinerator Wheel - Asroni; Bambang Surono; Hendri Yonatan (Universitas Muhammadiyah Sidoarjo, 2025)
An incinerator is a high-temperature waste-burning device with a closed, insulated combustion chamber, designed to minimize environmental impact [1]. Modern incinerators aim to reduce inorganic waste and smoke emissions, particularly in Metro City, Lampung Province [2]. A key component is the wheel, which reduces friction and enhances mobility [3]. This study focuses on designing the incinerator wheel, determining its geometry and material, and analyzing stress, strain, and deformation through simulation [4]. The design process used Autodesk Inventor Professional, while simulations were performed in SolidWorks [5]. Tests were conducted under three load conditions: no load, 250 kg, and 500 kg. The final wheel design measures 150 mm in diameter, 50 mm in width, and 10 mm in thickness, using cast iron. Simulation results show stress, strain, and deformation remain below material limits, even at 500 kg load, confirming the wheel’s safety and reliability for optimal incinerator performance.